2014
DOI: 10.5811/westjem.2014.4.20489
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Proactive Risk Analysis to Emergency Department Sickle Cell Care

Abstract: IntroductionPatients with sickle cell disease (SCD) often seek care in emergency departments (EDs) for severe pain. However, there is evidence that they experience inaccurate assessment, suboptimal care, and inadequate follow-up referrals. The aim of this project was to 1) explore the feasibility of applying a failure modes, effects and criticality analysis (FMECA) in two EDs examining four processes of care (triage, analgesic management, high risk/high users, and referrals made) for patients with SCD, and 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A FMECA is an engineering method, used initially in high‐risk industries such as aerospace and nuclear power, 25 , 26 but increasingly applied to health care. 27 , 28 , 29 , 30 , 31 , 32 A FMECA involves engaging stakeholders to describe and depict the steps and workflows of a process and then to identify, characterize, and rank the safety vulnerabilities or failures of each step in the process in a risk table that permits rank ordering of the failures. FMECAs help to counter most organizations’ common temptation to focus on process solutions for the most evident and visible failures, which may not be the same.…”
Section: Methodsmentioning
confidence: 99%
“…A FMECA is an engineering method, used initially in high‐risk industries such as aerospace and nuclear power, 25 , 26 but increasingly applied to health care. 27 , 28 , 29 , 30 , 31 , 32 A FMECA involves engaging stakeholders to describe and depict the steps and workflows of a process and then to identify, characterize, and rank the safety vulnerabilities or failures of each step in the process in a risk table that permits rank ordering of the failures. FMECAs help to counter most organizations’ common temptation to focus on process solutions for the most evident and visible failures, which may not be the same.…”
Section: Methodsmentioning
confidence: 99%
“…Data for this project were reported in the context of a two-center QI project. 17 , 18 Details of the project have been published. 17 20 Briefly, the project attempted to optimize the treatment of VOC in the ED using best practices, 1 while monitoring healthcare utilization and psychosocial referral needs and practices.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of a two-center quality improvement (QI) project designed to implement best practices for the ED management of patients with complications of sickle cell disease, 17 , 18 we had a unique opportunity to prospectively examine the impact of different utilization rates of DH care, and/or EDOU care on rates of hospital admission for patients with sickle cell anemia experiencing VOC. We also had the opportunity to assess ED encounters and hospitalizations for our two cohorts of patients at outside centers within a 20-mile radius of each study site, an aspect of care rarely reported on.…”
Section: Introductionmentioning
confidence: 99%